Assessment of Supply Chain Sustainability Strategy on Sustainable Performance Indicators: Evidence from Siemens DEGREE Framework (2019-2023) - Zaye, Ejiro; Ogunyomi-Oluyomi, Oluwatosin (International Journal of Supply Chain and Logistics, 2025)
Purpose: Since the incessant supply chain disruptions, the need for supply chain sustainability strategy becomes a veritable tool for a competitive advantage in all disciplines, sectors and governance. This study is motivated to empirically investigate the effects of supply chain sustainability strategy on sustainable performance indicators in the manufacturing technology sector. Methodology: The study employs a purposive sampling technique and selected Siemens Company to analyses the Siemens DEGREE sustainability strategy framework. Secondary data from Siemens sustainability reports and annual reports from 2019 to 2023 were analyzed using descriptive analysis. Findings: Findings reveals that decarbonization of the DEGREE Key Performance indicators has consistently achieve all decarbonization key performance indicators by Siemens targets and also met the SDGs GHG emissions targets by 2030. Unique Contribution to Theory, Practice and Policy: Stakeholder theory was preferred over the Triple Bottom Line in this study because the stakeholder theory represents the DEGREE sustainability strategy framework implemented by Siemens to assess the key sustainable performance indicators (KPI). Recommendations to Siemens include use of biodiversity partnership, eco-design technology, tree-planting volunteering campaign, to reduce waste-to-landfill as well as intensive equitable access to career opportunities and offer a higher pay to encourage more digital learning hours per employee for career growth that will meet all DEGREE sustainability performance before 2025 as well as the SDGs by 2030.